2015
DOI: 10.1111/dme.12834
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and health‐related quality of life in patients with Type 2 diabetes

Abstract: Vitamin D status was not associated with health-related quality of life in patients with Type 2 diabetes. This could be explained by the relatively high serum 25-hydroxyvitamin D concentration, good glycaemic control and relatively good health-related quality of life of all patients. A prospective study among patients with vitamin D deficiency and poor glycaemic control would be interesting for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…There was no benefit of vitamin D in improving perceived physical health in the current study. One recent cross-sectional study of persons with T2DM ( n = 241) reported no association between vitamin D levels (grouped as <50 nmol/l and >50 nmol/l) and their perceived physical or mental health (using the SF-36) [ 58 ]. Similarly, a systematic review reported no overall association between vitamin D supplementation and health-related quality of life (using the SF-36).…”
Section: Discussionmentioning
confidence: 99%
“…There was no benefit of vitamin D in improving perceived physical health in the current study. One recent cross-sectional study of persons with T2DM ( n = 241) reported no association between vitamin D levels (grouped as <50 nmol/l and >50 nmol/l) and their perceived physical or mental health (using the SF-36) [ 58 ]. Similarly, a systematic review reported no overall association between vitamin D supplementation and health-related quality of life (using the SF-36).…”
Section: Discussionmentioning
confidence: 99%
“…However, greater than 90% of this number is either overweight or obese [3]. Diabetes mellitus has a high impact on morbidity and mortality as diabetes mellitus associated with 2-4 fold risk for cardiovascular diseases and stroke in addition, diabetes is considered as a leading cause of renal disorders [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The recent studies indicate that vitamin D deficiency may increase diabetes risk (13). Scientific studies draw our attention to effects of vitamin D on diabetes and glucose control (14,15). According to recent studies, vitamin D deficiency affects glucose metabolism and actually causes diabetes rather than obesity (16,17).…”
Section: Discussionmentioning
confidence: 99%